Relationship between Stage of Diabetic Retinopathy and Pulse Wave Velocity in Japanese Patients with Type 2 Diabetes - Kumiko Tanaka; Toshihide Kawai; Yoshifumi Saisho; Shu Meguro; Kana Harada; Yuka Satoh; Kaori Kobayashi; Kei Mizushima; Takayuki Abe; Hiroshi Itoh (Journal of Diabetes Research)
Objectives. We investigated the relationship between the stage of diabetic retinopathy and pulse wave velocity (PWV). Methods. This was a cross-sectional study of 689 patients (406 men and 283 women) with type 2 diabetes who were admitted to our hospital from 2004 to 2007. Brachial-ankle pulse wave velocity (baPWV) was measured by an arterial pressure measurement device as PWV/ABI. Diagnosis of diabetic retinopathy was made by ophthalmologists based on the Davis classification: no diabetic retinopathy (NDR), simple retinopathy (SDR), pre-proliferative retinopathy (pre-PDR), and proliferative retinopathy (PDR). Results. There was a significant difference in PWV between patients without diabetic retinopathy (1657.0±417.9 m/s (mean ± SD)) and with diabetic retinopathy (1847.1±423.9 m/s) (P<0.001). In addition, the stage of diabetic retinopathy was associated with aortic PWV (1657.0±417.9 m/s in NDR (n=420), 1819.4±430.3 m/s in SDR (n=152), 1862.1±394.0 m/s in pre-PDR (n=54), and 1901.1±433.5 m/s in PDR (n=63) (P<0.001)). Conclusions. In patients with diabetic retinopathy, even in those with SDR, PWV was higher than that in patients without diabetic retinopathy. Physicians should therefore pay attention to the value of PWV and macroangiopathy regardless of the stage of diabetic retinopathy.